The English Presbyterian messenger: Volume 11(1859), Issue 143 ((ATLA serials preservation program ; ATLA film 2006C-S009)., 1859)
Reel 1. v. 1:19 - v. 6:84 (Oct 1846-Dec 1854). -- Reel 2. v. 8:107 - v. 15:188 (Nov 1856-Aug 1863).